A food systems approach and qualitative system dynamics model to reveal policy issues within the commercial broiler chicken system in South Africa - Queenan, K.; Cuevas, S.; Mabhaudhi, Tafadzwanashe; Chimonyo, M.; Shankar, B.; Slotow, R.; Hasler, B. (2022)
Global broiler production and consumption levels continue to rise. South Africa’s broiler system is dominated by commercial production and formal retail trade, with competition from cheap imports. Local broiler policies have narrow, production-driven, short-term aims for industry growth and national food security. However, these have unintended consequences that undermine the system’s future sustainability. Using a food systems approach, this study developed a qualitative system dynamics model of the South African commercial broiler system and used it to engage stakeholders in policy discussions within the boundaries of health, nutrition, and environmental sustainability. A problem statement and key system elements were drawn from a previously published qualitative study and were validated by 15 stakeholders via an online questionnaire. From this, a seed model was developed, expanded into a larger model, and shared in a modular format with stakeholders in virtual meetings, on an individual or institutional basis, for feedback and validation, and for discussion of areas for policy consideration. Refinements were incorporated into the modules, policy considerations were summarised, and crosscutting issues were identified. The model demonstrated the system’s complexity, interlinkages, feedbacks, reinforcing and balancing loops, and behaviour archetypes. The modular presentation format created a suitable platform for stakeholder engagement. Current policies focus on local commercial production, formal markets, and affordability without cognisance of the broader system represented by the model. Inequality pervades throughout the system. Commercial producers, linked to large supermarkets and fast-food chains, dominate the system, presenting barriers to entry. Affordability is unintentionally traded off against non-communicable disease risks through brining of most frozen products, and ultra-processing of fast-food items. Foodborne disease control is critical, given the proportion of vulnerable individuals, and greater coherence of food safety policy is urgently needed. The environmental footprint of broilers, whilst less than that of ruminants, deserves closer scrutiny based on its dependence on intensive cereal production for feed. This study’s food systems approach provides a system-wide perspective and a foundation for policymakers to develop more integrated and transformative policies.